Political Parties and Women’s Representation in the Indonesian Parliament 2009-2019 - Ruriana, Alvinda Putri; Fahadayna, Adhi Cahya; Tawakkal, George Towar Ikbal (Political Science Program, Universitas Negeri Semarang, 2023)
As the transmission belt linking people's aspirations to the government, the political party has a crucial role in preparing actors to become candidates for people's representatives. Since the enactment of affirmative policies both in elections and internal parties, the number of women in parliament has never met the 30% quota as expected. During the ten years from 2009 to 2019, the number of women in the House of Representatives (Dewan Perwakilan Rakyat, DPR) seats only ranged from 17-20 percent. This article examines the influence of political parties' characteristics on women's representation in the Indonesian parliament in the 2009-2019 period. This research uses four party characteristics by Sundström Stockemer as variables that will be analyzed through linear regression models. The research results show that the vote size variable is the only variable significantly influencing women's representation in parliament. The estimated trend of women's representation in parliament shows an increase in the upcoming 2024 elections. However, it is still far from the target of 30%. Hence, it needs a progressive affirmative policy in the form of reserved seats to encourage proportionality in the policy-making forum.